Morbidity status of slum dwelling children of lucknow city - Khanna, Anish; Jain, V C; Srivastava, V K; Jain, Savita; Mohan, Uday (Indian Journal of Community Health, 1995)
The presen study was carried out to find out the level of morbidity among slum childreni aged 5-14 years, It was found tha t46.4% of children were ill at the lime of study. The prevalence of various illnesses hcu studied. An aiuilysis of morbidity with social variables mi not found to be significant. 19.3% children has dental disorders and 45.8% children has parasites infestation of llieG I Tract. 57.6% of children vere having one or the other behavioural problems.